2007
DOI: 10.1021/ja068002s
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching Pathways in Single-Molecule FRET Experiments

Abstract: In order to acquire accurate structural and dynamical information on complex biomolecular machines using single-molecule fluorescence resonance energy transfer (sm-FRET), a large flux of donor and acceptor photons are needed. To achieve such fluxes one may use higher laser excitation intensity, however this induces increased rates of photobleaching. Anti-oxidants additives have been extensively used for reducing acceptor's photobleaching. Here we focus on deciphering the initial step along the photobleaching p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 28 publications
3
89
0
Order By: Relevance
“…Empirically, we found that the excitation wavelength commonly determines the photobleaching pathway, that is, ROXS works best at longer excitation wavelength. [20,109,110] The generality of the concept is further underscored by the broad range of redox-active compounds including for example, ascorbic acid, trolox, mercaptoethylamine and ferrocene derivatives as reductants and MV, nitrobenzoic acid, 4-nitrobenzyl alcohol and troloxquinone as oxidants. [20,21,105,111] In this context, it is interesting to note that the antifading mechanism of trolox could be resolved studying the blinking of single oxazine molecules with functioned as quantitative sensors for reductants and oxidants (a single-molecule redox sensor).…”
Section: The Reducing and Oxidizing System (Roxs): Controlling The Flmentioning
confidence: 99%
“…Empirically, we found that the excitation wavelength commonly determines the photobleaching pathway, that is, ROXS works best at longer excitation wavelength. [20,109,110] The generality of the concept is further underscored by the broad range of redox-active compounds including for example, ascorbic acid, trolox, mercaptoethylamine and ferrocene derivatives as reductants and MV, nitrobenzoic acid, 4-nitrobenzyl alcohol and troloxquinone as oxidants. [20,21,105,111] In this context, it is interesting to note that the antifading mechanism of trolox could be resolved studying the blinking of single oxazine molecules with functioned as quantitative sensors for reductants and oxidants (a single-molecule redox sensor).…”
Section: The Reducing and Oxidizing System (Roxs): Controlling The Flmentioning
confidence: 99%
“…8–15 However, smFRET has limited resolution of very fast events 27 and no capacity for long-duration monitoring of a single molecule. 28 For example, no smFRET measurement has measured more than three successive nucleotide incorporation events by the same KF molecule 9 . Rather than focusing on enzyme turnover, several smFRET experiments used a dideoxy substrate, which elegantly probes conformational dynamics during molecular recognition of the nucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…The main issue is time resolution. Current SM-FRET dyes saturate at photon emissions of approximately 100 kHz (31), restricting the effective time resolution to the 0.5-1 ms it takes to detect statistically significant numbers of photons. We optimized the time-resolution/ photodamage trade-off by performing chemical-denaturation experiments at 279 K (which slows down BBL kinetics by approximately 200-fold) in conjunction with a newly developed photoprotection cocktail that affords emissions of approximately one photon per microsecond with little photodamage (32).…”
mentioning
confidence: 99%